2018
DOI: 10.1186/s12935-018-0573-4
|View full text |Cite
|
Sign up to set email alerts
|

Vasodilator-stimulated phosphoprotein (VASP), a novel target of miR-4455, promotes gastric cancer cell proliferation, migration, and invasion, through activating the PI3K/AKT signaling pathway

Abstract: BackgroundMicroRNAs (miRNAs) are small non-coding RNAs which play important roles in the carcinogenesis of gastric cancer (GC). Expression profiling of miRNAs in paired gastric cancer and adjacent normal gastric tissues has demonstrated that miR-4455 is down-regulated in gastric cancer tissues, but its functional role in the carcinogenesis of GC had not previously been investigated.AimsThe purpose of this study was to investigate the functional and biological mechanisms of miR-4455 in the progression of GC, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 46 publications
(35 reference statements)
1
11
0
Order By: Relevance
“…Consistently, miR-4455 increased apoptosis and reduced proliferation, invasion and migration in a gastric cancer cell line (MGC-803) (Chen et al 2018). MiR-4455 targets VASP 3'-UTR and a decrease in VASP levels results in PI3K/AKT inhibition (Chen et al 2018). VASP is a key mediator of actin cytoskeleton remodeling, polarization and cell migration (Krause et al 2003;Bailly 2004).…”
Section: Discussion____________________________________________________mentioning
confidence: 90%
“…Consistently, miR-4455 increased apoptosis and reduced proliferation, invasion and migration in a gastric cancer cell line (MGC-803) (Chen et al 2018). MiR-4455 targets VASP 3'-UTR and a decrease in VASP levels results in PI3K/AKT inhibition (Chen et al 2018). VASP is a key mediator of actin cytoskeleton remodeling, polarization and cell migration (Krause et al 2003;Bailly 2004).…”
Section: Discussion____________________________________________________mentioning
confidence: 90%
“…miR-99b-5p/203a-3p and miR-99b-5p/203a-3p may function as tumor suppressive miRNAs by negatively regulating IGF-1R expression in GC cells [15]. miR-4455 functions as a tumor suppressor in GC by targeting VASP, leading to the activation of the PI3K/AKT signaling pathway and inhibition of VASP-mediated proliferation, migration, and invasion of GC cells [16]. miR-23a/27a/24-2 cluster may mediate the progression of GC through the suppression of SOCS6 expression [17].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al showed that miRNA-610 inhibits the invasion of gastric cancer cells by suppressing the expression of VASP, which could be used therapeutically to inhibit gastric cancer progression and metastasis [238]. VASP is inhibited by miR-4455 functions as a tumor suppressor in gastric cancer cells which decreased VASP-mediated proliferation, migration, and invasion [239]. In hepatocellular carcinoma (HCC) hypoxia upregulated VASP by binding to hypoxia response elements (HRE) in the VASP promoter region.…”
Section: Ena/vasp In Cancermentioning
confidence: 99%